Pengaruh Perbandingan Tepung Terigu Dengan Tepung Labu Kuning Terhadap Organoleptik Roti Tawar - Putri, Rani Fatikha; Puspaningrum, Yessita (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2022)
Summer squash In general, the community is only processed as compote, boiled or steamed. Researchers have an idea to create innovations in processed pumpkin, namely by making pumpkin flour to then be made into plain bread with a ratio of wheat flour and pumpkin flour. This study used the RAL method with 3 levels and 3 repetitions, so that in this study 9 experimental units were obtained. With a combination of K1: 225 grams of wheat flour: 25 grams of pumpkin flour, K2: 200 grams of wheat flour: 50 grams of pumpkin flour, K3: 75 grams of flour: 175 grams of pumpkin flour. Data analysis used quantitative methods. The process of making pumpkin flour by stripping the skin and removing the nets, washing, cutting / reducing size, drying, grinding and sifting. The process of making white bread with a ratio of wheat flour and pumpkin flour begins with the process of kneading, developing, printing, improving and baking. The acceptance variable that is of interest to the K1 combination is 90% wheat flour and 10% pumpkin flour. Keywords: Pumpkin, Pumpkin Flour, Organoleptic